Female labour supply in farm households: farm and off-farm participation - Callan, Tim; Van Soest, Arthur (Economic & Social Studies, 1993)
Many Irish women in farm households have an input into the running of the farm; while a much smaller proportion are engaged in off-farm employment. Using cross-section household data, we analyse various models in which farm wives choose between farm work, off-farm paid work, and other (home production) activities. The explanatory variables include family characteristics, farm characteristics and the woman's potential wage rate for off-farm employment. We compare probit- and logit-type models and allow for wage rate endogeneity. The main finding according to all models is the very large sensitivity of off-farm participation with respect to the wage.
Keywords: Female labour; Farm households; Women in farming; Ireland